Eficiência, processo penal e Constituição Federal: uma análise diante da retomada da execução provisória da pena pelo Supremo Tribunal Federal - Vilela, Augusto Tarradt (Universidade do Vale do Rio dos Sinos, 2018)
A crisis in criminal law derived from several factors was established, in a world order, also specifically in Brazil, and many of these were diagnosed by Silva Sánchez in the framework of the expansion of criminal law. This crisis has caused the population to demand more interference of criminal law in the resolution of daily social conflicts, removing the exceptional character of criminal law. The movement, captained by the banner of the fight against corruption and impunity, has generated effects in the social context, and even reached jurists and, more punctually, the Federal Supreme Court, which under pressure tried to respond to the aspirations of Brazilian society, in especially for reasons of political crisis. The consequences of these requirements in the Constitutional Court can be verified by the efficiency provided in the scope of the decision issued in habeas corpus n. 126.292/SP (and others) that modified the understanding of the Supreme Court to allow the condemnation to be served before the final sentence. In the elapse of decisions, the presence of the pragmatism and even of utilitarianism is visible. In view of this, it is intended to identify the efficiency model applied by the Supreme Court in the decisions that enabled the resumption of the provisional execution of the condemnation and, in view of the efficiency vision of Wedy and the concept of adequate response to the Federal Constitution of Streck, propose a constitutionally adequate and, if not, what is the correct model.
Keywords: Eficiência; Processo penal; Execução provisória; Constituição Federal; Efficiency; Criminal procedure; Provisional execution; Federal constitution; ACCNPQ::Ciências Sociais Aplicadas::Direito